INCREASING STUDENTS’ NARRATIVE PARAGRAPH WRITING ABILITY THROUGH THE USE OF PICTURE SEQUENCE - Aisyah Sunarwan (State Institute for Islamic Studies IAIN of Metro, 2016)
The aim of teaching foreign language is defined in terms of four skills, listening, speaking, reading and writing. Writing as one of the four skill is often ignored, this may be do to a number of factors, such as time consuming of correcting, low motivation, limited time to study writing and lack of teaching technique used. The objective of the study is to investigate whether the use of picture sequence increase the students’ narrative paragraph writing ability especially in making good content, organization (form), using right vocabulary, correct grammar and mechanic in a paragraph at the Eighth Grade of State Junior High School 3 Batanghari. In this research, the researcher and collaborator did classroom action research which is portrayed as a cyclical spiral process involving steps of planning, acting, observing and reflecting. The research was conducted through collaborative with an English teacher of State Junior High School 3 Batanghari. In this research, students did pre-test before having treatment and after that they should do the post-test cycle 1 and cycle 2. From the analysis in pre-test and post-test cycle 1, there was an increasing from the students result score. It is proved from their score 53,14 became 5,9. At the first cycle, we found the students’ problem was in grammar, such as capitalization and simple pat tense. In vocabulary, they couldn’t perform their writing in correct English vocabulary. While in mechanic, students tended to write the punctuation marks exaggeratedly which actually no need at all. In the second cycle, few students still had some problems in grammar in mechanic, but most of them had improved their writing ability, it was proved from their result score from post-test cycle 1 5,9 became 70 at post-test cycle 2. It means that the use of picture sequence can increase the students’ narrative paragraph writing ability.